Mitochondria-associated microRNAs in rat hippocampus following traumatic brain injury - Wang, Wang-Xia; Visavadiya, Nishant P.; Pandya, Jignesh D.; Nelson, Peter T.; Sullivan, Patrick G.; Springer, Joe E. (Experimental neurology, 2015)
Traumatic brain injury (TBI) is a major cause of death and disability. However, the molecular events contributing to the pathogenesis are not well understood. Mitochondria serve as the powerhouse of cells, respond to cellular demands and stressors, and play an essential role in cell signaling, differentiation, and survival. There is clear evidence of compromised mitochondrial function following TBI; however, the underlying mechanisms and consequences are not clear. MicroRNAs (miRNAs) are small non-coding RNA molecules that regulate gene expression post-transcriptionally, and function as important mediators of neuronal development, synaptic plasticity, and neurodegeneration. Several miRNAs show altered expression following TBI; however, the relevance of mitochondria in these pathways is unknown. Here, we present evidence supporting the association of miRNA with hippocampal mitochondria, as well as changes in mitochondria-associated miRNA expression following a controlled cortical impact (CCI) injury in rats. Specifically, we found that the miRNA processing proteins Argonaute (AGO) and Dicer are present in mitochondria fractions from uninjured rat hippocampus, and immunoprecipitation of AGO associated miRNA from mitochondria suggests the presence of functional RNA-induced silencing complexes. Interestingly, RT-qPCR miRNA array studies revealed that a subset of miRNA is enriched in mitochondria relative to cytoplasm. At 12h following CCI, several miRNAs are significantly altered in hippocampal mitochondria and cytoplasm. In addition, levels of miR-155 and miR-223, both of which play a role in inflammatory processes, are significantly elevated in both cytoplasm and mitochondria. We propose that mitochondria-associated miRNAs may play an important role in regulating the response to TBI. •MiRNA machinery proteins Argonaute and Dicer are present in hippocampal mitochondria.•Several miRNAs are enriched in hippocampal mitochondria under normal conditions.•Numerous mitochondria-associated miRNAs are significantly altered following TBI.•MiRNAs enriched in mitochondria decreased and cytosolic levels increased after TBI.